The impact of digital transformation on open innovation performance: The intermediary role of digital innovation dynamic capability. - Peiyao Qiu; Benrui Chang (PLoS ONE)
In the context of digital economy, both the process and boundaries of open innovation performance are changing, and digital transformation has become an important factor for enterprises to realize open innovation performance in a complex and changing environment. This study based on the dynamic capability theory, etc. to explore how digital transformation drives the open innovation performance of enterprises and analyze its impact effects as well as the internal mechanism of action. In this paper, A-share listed companies in China's Shanghai and Shenzhen cities from 2008-2022 are selected as research samples for empirical tests, and the research results show that digital transformation significantly stimulates enterprises' open innovation performance, which still holds true after relying on a series of robustness tests. The study on the mechanism of action shows that digital transformation mainly enhances the dynamic capability of digital innovation, and ultimately promotes the open innovation performance of enterprises. And environmental dynamics play a positive moderating role. Heterogeneity analysis shows that the incentive effect of digital transformation on open innovation performance is more obvious in enterprises with high-tech and non-state ownership. Based on the new perspective of digital innovation dynamic capability, this study further reveals the effect and mechanism of digital transformation on open innovation performance, and provides theoretical basis and decision-making reference for enterprises to utilize the opportunity of digitalization to achieve open innovation performance results.